Re-evaluating Creativity : The Individual, Society and Education - Hernández-Romero, Lili (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book proposes a groundbreaking approach to the study of personal creativity, linking this to the analysis of the chakras, or centers of energy, of the subtle system suggested by the Eastern philosophy called Sahaja Yoga. The author argues that creativity is to be re-learnt through a process of self-review, a self-examination which is underpinned by the author's concept of the outsider to the self, a pervasive condition characterized by a tendency to be connected to the outer world at the expense of the inner world. The author analyses creativity from three different but interrelated frameworks - cultural studies, social psychology, and education - and maps out a route that may take the individuals into an understanding of blockages in their creative process. It also considers examines aspects that have contributed to sustain the condition of the outsider to the self, hindering the creativity of individuals and argues that the traditional education system is discussed as constricting and releasing factor of creativity. Finally, through the use of auto-ethnography, the author reveals a process of blocked and unblocked creativity. This book is a key read for all those interested in psychology, cultural studies, creativity and education.- Resumé vydavatel
Keywords: kreativita; tvůrčí myšlení; vzdělávání; creative ability; creative thinking; education; elektronické knihy; monografie; electronic books; monographs